The mammalian cell cycle: the autonomous stage and cell cycle targets in cancer therapy - Blain, Stacy (Henry Stewart Talks, 2023)
Proliferative and antiproliferative signals, Oncogenic funnel, Cyclins and CDKs, Mitogenic signals, Retinoblastoma protein, Mitosis, Cell arrest, Chemotherapy, Target-specific cancer therapy, Palbocicib-PALOMA 3